Does It Pay to Compete Aggressively? Contingent Roles of Internal and External Resources. (February 2019) - Andrevski, Goce; Ferrier, Walter J.
We examine, in hypercompetitive environments, why some firms fail to benefit from competitive aggressiveness while others experience superior profits. We explore the relationship between competitive aggressiveness and performance in a sample of 141 firms from three hypercompetitive industries—personal computers, computer-aided software engineering, and semiconductors—from 1995 to 2006. Contrary to the predominant view within competitive dynamics research, we find that competitive aggressiveness is not a universally effective strategy. For some firms, excessive competitive aggressiveness can escalate costs and diminish performance. Using polynomial regression analysis and response surface methodology, we identify the conditions under which competitive aggressiveness enhances firm performance. Our findings reveal that firms benefit from competitive aggressiveness when they have specialized technological resources and support from a dense network of alliance partners.